ELECTROENCEPHALOGRAPHIC ANALYSIS OF BRAIN WAVE BEHAVIOR DURING STATIC AND DYNAMIC POSTURAL CONTROL IN INDIVIDUALS WITH CONGENITAL BLINDNESS (CIPEEX, 2025)
Postural control is characterized by neuromuscular corrections and/or monitoring of stability limits, involving increased processing of sensory information due to postural demands. The lack of vision disrupts postural control and, consequently, affects body balance. However, data on brain waves to monitor the maintenance of static and dynamic postural stability in individuals with total blindness are scarce. This study describes a protocol that compares the differences in brain wave behavior during the maintenance of static and dynamic postural control between individuals with total blindness and individuals with vision. We will evaluate delta (1-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (12-30 Hz), and gamma (> 50 Hz) waves during postural stability assessments, functional mobility (i.e., Timed Up and Go test), and 3D gait. Through this study, we will seek to better understand the patterns of brain activity when postural control is challenged by sensory systems (i.e., somatosensory and visual) and explore possible changes in brain waves induced by assistive devices, such as a cane, during functional mobility and gait. In practice, this study is fundamental for the development of rehabilitation strategies to promote better functional independence, improving movement quality and attenuating the risks associated with joint degeneration and falls.
Keywords: electroencephalography; brain waves; postural control; visual impairment